PERSEPSI USTADZAH TERHADAP METODE AL-MIFTAH LIL ULUM DALAM MENINGKATKAN PEMAHAMAN NAHWU DAN SHARAF BAGI SANTRI PEMULA DI PONDOK PESANTREN RAUDLATUL ULUM 1 PUTRI - Milatul Fauziyah; Abdulloh Abdulloh (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to examine the perceptions of female teachers towards the application of the Al-Miftah Lil Ulum method in improving the understanding of nahwu and sharaf for beginner students at the Raudlatul Ulum 1 Putri Islamic Boarding School. The Al-Miftah Lil Ulum method is a method of learning the science of tools that is structured concisely, systematically, and gradually as an introduction to understanding the yellow book. This study uses a qualitative approach with a type of field research conducted in natural conditions. The research subjects consisted of five female teachers teaching the Al-Miftah Lil Ulum Book and several beginner students as sources of triangulation data. Data collection techniques were carried out through interviews, observation, and documentation, while data analysis used an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation of sources and techniques. The results of the study indicate that female teachers have a positive perception of the Al-Miftah Lil Ulum method because it is considered effective, easy to understand, and able to increase students' learning motivation. This method helps students understand the basic rules of grammar and grammar, recognize Arabic sentence structure, and begin to read the yellow books. However, there are obstacles such as differences in student ability, limited learning time, and the difficulty level of the material in certain volumes. This research confirms that the role of the female teacher is crucial to the success of implementing the Al-Miftah Lil Ulum method.